Diet Quality Index associated with Digital Food Guide: update and validation - Simone Caivano; Fernando Antonio Basile Colugnati; Semíramis Martins Álvares Domene
Monitoring and assessing dietary intake may favor the promotion of healthy choices and the indexes that assess the quality of the diet contribute to this purpose. The Diet Quality Index associated with the Digital Food Guide (DQI-DFG) was developed from guidelines of the School of Public Health at Harvard University, adjusted for the Brazilian food habits. Based on new studies on prevention of chronic non-communicable diseases, the objective of this study was to improve and validate the DQI-DFG for a second version. The following psychometric properties were used: (a) content validation: consensus on healthy eating and DQI among experts; (b) construct validation: enhancement of a reference diet to determine recommended serving sizes and consumption ranges; correlation between each group score and energy value; comparative analyses between menu assessment by experts and DQI-DGF results to confirm the score criterion; (c) reliability: agreement between the result shown by the evaluators and the result presented by DQI-DFG; correlation between each food group score and total DQI score to understand the relationship between these variables. The energetic values do not influence the DQI score. There is a high correlation between the score attributed by experts and the result of DQI-DFG (r = 0.78 until r = 0.97). The Index components have a balanced score of influence in its final result (r = 0.49 until r = 0.10). Consensus result performed among experts legitimates the concepts that justify DQI-DFG. There was an agreement between menu quality evaluation by experts and the results shown by DQI-DFG.